Measurement of top quark pair differential cross-sections in the dilepton channel in pp collisions at s√ = 7 and 8 TeV with ATLAS - Aaboud, M. (2016)
Measurements of normalized differential cross-sections of top quark pair (t t  ̄ ) production are ̄presented as a function of the mass, the transverse momentum and√ the rapidity of the t t sys-tem in proton-proton collisions at center-of-mass energies of s = 7 TeV and 8 TeV. Thedataset corresponds to an integrated luminosity of 4.6 fb −1 at 7 TeV and 20.2 fb −1 at 8 TeV,recorded with the ATLAS detector at the Large Hadron Collider. Events with top quark pairsignatures are selected in the dilepton final state, requiring exactly two charged leptons and atleast two jets with at least one of the jets identified as likely to contain a b-hadron. The mea-sured distributions are corrected for detector effects and selection efficiency to cross-sectionsat the parton level. The differential cross-sections are compared with different Monte Carlogenerators and theoretical calculations of t t  ̄ production. The results are consistent with themajority of predictions in a wide kinematic range.